O financiamento do esporte de alto rendimento no Brasil: uma análise do programa "Brasil no Esporte de Alto Rendimento" (2004-2011) - Barboza Eiras de Castro, S.; Poffo, B. N.; Lange de Souza, D. (Revista Brasileira de Ciência e Movimento, 2016)
There are just a few studies on sports funding in Brazil, which hinders the social control of public investments in the area. Thus, the aim of this study was to investigate the distribution of authorized and executed budget among the planned actions and among the federal agencies involved with the program "Brazil in Elite Sport" from 2004 to 2011. This research was quantitative and descriptive. Data were collected in the "Portal Siga Brasil" and analyzed with the support of Microsoft Office Excel (2007) and Statistical Package for Social Sciences (v. 22). We found that the budgetary resources of the program showed significant growth from 2008 due to the hosting of major sporting events and increased investments in other government actions for elite sport. The major sports events amounted to 65.5% of the executed funds in the program. Other actions received 34.5% of these funds. Despite the increase of investments in elite sport, actions related to infrastructure and science and technology applied to sports, as well as the detection of sport talents and the training of athletes suffered budget discontinuities. The correction of these discontinuities constitutes a challenge to the development of elite sport in the country.